ANALYSIS OF SIMILARITIES BETWEEN SOCRATES AND CONFUCIUS - TianBo, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2023)
Abstract: Socrates and Confucius are important figures in the history of early human thought. A comparison of Socrates and Confucius's life pursuits, life trajectories, ways of thinking, and contents of thought reveals many thought-provoking questions about ancient Greece and ancient China, it would be helpful to have a better and more objective understanding of world civilization.